Antibiotic Resistance and Mechanisms of Pathogenic Bacteria in Tubo-Ovarian Abscess - Tang, Huanna; Zhou, Hui; Zhang, Runju (Frontiers in Cellular and Infection Microbiology, 2022)
A tubo-ovarian abscess (TOA) is a common type of inflammatory lump in clinical practice. TOA is an important, life-threatening disease, and it has become more common in recent years, posing a major health risk to women. Broad-spectrum antimicrobial agents are necessary to cover the most likely pathogens because the pathogens that cause TOA are polymicrobial. However, the response rate of antibiotic treatment is about 70%, whereas one-third of patients have poor clinical consequences and they require drainage or surgery. Rising antimicrobial resistance serves as a significant reason for the unsatisfactory medical outcomes. It is important to study the antibiotic resistance mechanism of TOA pathogens in solving the problems of multi-drug resistant strains. This paper focuses on the most common pathogenic bacteria isolated from TOA specimens and discusses the emerging trends and epidemiology of resistant Escherichia coli, Bacteroides fragilis, and gram-positive anaerobic cocci. Besides that, new methods that aim to solve the antibiotic resistance of related pathogens are discussed, such as CRISPR, nanoparticles, bacteriophages, antimicrobial peptides, and pathogen-specific monoclonal antibodies. Through this review, we hope to reveal the current situation of antibiotic resistance of common TOA pathogens, relevant mechanisms, and possible antibacterial strategies, providing references for the clinical treatment of drug-resistant pathogens.